New Reforms in Kenya - Munene, Ishmael (International Higher Education, 2013)
Kenya has implemented a significant national reform of its higher education system in an effort to include both public and private higher education equally. Kenya's problems of rapid expansion, inadequate quality assurance, and declining quality are intended to be addressed.